The dark side of capitalism – in orthodox economics?. Issue 5 (3rd September 2019) - Zafirovski, Milan
Abstract: The article addresses the dark side of capitalism as an economic system, as identified and highlighted in orthodox, laissez-faire, including classical and neoclassical, economics. While orthodox economics is widely regarded as apologetic with respect to capitalism, still it to some extent recognizes or implies the latter's dark side and therefore its duality and complexity in terms of its economic and other outcomes. The paper identifies and considers certain salient manifestations of this face of capitalism such as those in the market, in economic welfare, in economic structure and the distribution of wealth, and others. The overall finding is that even orthodox economics does not consider capitalism to be an absolute good and an immutable, eternal, and perfect economic system, and instead acknowledges and emphasizes its relative character in societal and historical terms and its various adverse dimensions and imperfections. The paper contributes to a better understanding of classical and neoclassical economics' treatment of capitalism in relation to its conception within classical sociology.